ChemInform Abstract: Efficient Synthesis of Aryl Boronates via Zinc‐Catalyzed Cross‐Coupling of Alkoxy Diboron Reagents with Aryl Halides at Room Temperature. Issue 10 (March 2015) - Bose, Shubhankar Kumar; Marder, Todd B.
Abstract A novel Zn/NHC‐catalyzed cross‐coupling reaction of aryl and hetaryl iodide and bromides with diboron compounds (II) and (V) is reported.